(untitled) (Journal of Partial Differential Equations, 2016)
In this work we give necessary and sufficient conditions to have a maximum principle for nonlinear system involving singular (p,q)-Laplacian operators on bounded domain Ω of Rn and then we prove the existence of positive weak solutions for the same system by using the Browder theorem method.